Are we facing a noncommunicable disease pandemic?. Issue 1 (March 2017) - Allen, Luke
Abstract: The global boom in premature mortality and morbidity from noncommunicable diseases (NCDs) shares many similarities with pandemics of infectious diseases, yet public health professionals have resisted the adoption of this label. It is increasingly apparent that NCDs are actually communicable conditions, and although the vectors of disease are nontraditional, the pandemic label is apt. Arguing for a change in terminology extends beyond pedantry as the move carries serious implications for the public health community and the general public. Additional resources are unlocked once a disease reaches pandemic proportions and, as a long-neglected and underfunded group of conditions, NCDs desperately require a renewed sense of focus and political attention. This paper provides objections, definitions, and advantages to approaching the leading cause of global death through an alternative lens. A novel framework for managing NCDs is presented with reference to the traditional influenza pandemic response.